Medical Texture Recognition Based on Intelligent Technique - Hasanen S. Abduallah; Hajer Mazin Salih (Engineering and Technology Journal, 2016)
The aim of this paper is to improve a disease diagnosing system through classifying the skin diseases depending on the skin images of many patients by using the multiwavelet transformation. First, extract features from multiwavelet coefficients. Second, the skin images are classified as Warts, Vitiligo, Hemangioma, and Normal depending on the decision rules generated by the decision tree using the ID3 learning algorithm.